Pengaruh Loan To Deposit Ratio (LDR) Dan Debt To Equity Ratio (DER) Terhadap Nilai Perusahaan Dimediasi Profitabilitas (ROA) Pada Perusahaan Perbankan Yang Terdaftar Di BEI Pada Periode 2020-2024 - Fadila Siti Nuraeni; Djalaludin Akbar; Mutiara Hayandani; Anggun Fitria Novianti; Alfiana Alfiana (INDO PUBLISHING, 2026)
This study aims to examine the influence of Loan to Deposit Ratio (LDR) and Debt to Equity Ratio (DER) on firm value with profitability (Return on Assets/ROA) as a mediating variable in commercial banks listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The Indonesian banking industry faced significant challenges due to the COVID-19 pandemic, which affected liquidity, capital structure, and profitability. The data reveal that LDR fluctuated, declining in 2020–2021 as banks adopted a conservative stance to maintain liquidity, and rising again in 2022–2024 in line with economic recovery. DER remained relatively stable but showed a downward trend post-pandemic, reflecting stronger equity positions and improved liability management. Meanwhile, ROA consistently increased, indicating enhanced efficiency in asset utilization to generate profits. This research contributes theoretically to the development of financial management and banking studies, while providing practical implications for bank management, investors, and regulators in optimizing liquidity, leverage, and profitability strategies to enhance firm value. By emphasizing ROA as a mediating variable, this study addresses research gaps and offers empirical evidence on the simultaneous impact of LDR and DER on profitability and firm value in Indonesia’s major banks.